1995
DOI: 10.1002/aheh.19950230107
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic release of amino acids from different humic substances

Abstract: Humic substances isolated from water, sediment, and soil were characterized by applying elemental analysis, spectroscopic analysis, and gelchromatographic molecular size distribution. In addition, the amounts and pattern of enzymatically released amino acids were determined. Depending on the origin of the humic substances, the percentage of released amino acid nitrogen related to the total nitrogen was in the range of 0.4 to 26.7Yo. The samples particularly differed in the content of leucine und tyrosine. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The nature of these materials is undergoing a major redefinition from a complex poly-condensed macromolecular structure (Schulten and Schnitzer 1993) to a less strongly bonded dynamic complex of smaller distinct molecules that include mainly plant and microbial constituents and their partial decomposition products held together by H-bonding, hydrophobic interactions and covalent bonds (Burdon 2001;Piccolo 2001;Sutton and Sposito 2005;Kleber et al 2006, this volume;). The presence of protein in humic extracts has been implied by release of amino acids by acid hydrolysis (Bremner 1965) and proteolytic enzymes (Ladd and Brisbane 1967;Jahnel and Frimmel 1995). Knicker and Hatcher (1997) and Zang et al (2000) have suggested that proteins might be provided long-term protection by their incorporation into hydrophobic domains of soil organic matter.…”
Section: Carbohydratesmentioning
confidence: 98%
“…The nature of these materials is undergoing a major redefinition from a complex poly-condensed macromolecular structure (Schulten and Schnitzer 1993) to a less strongly bonded dynamic complex of smaller distinct molecules that include mainly plant and microbial constituents and their partial decomposition products held together by H-bonding, hydrophobic interactions and covalent bonds (Burdon 2001;Piccolo 2001;Sutton and Sposito 2005;Kleber et al 2006, this volume;). The presence of protein in humic extracts has been implied by release of amino acids by acid hydrolysis (Bremner 1965) and proteolytic enzymes (Ladd and Brisbane 1967;Jahnel and Frimmel 1995). Knicker and Hatcher (1997) and Zang et al (2000) have suggested that proteins might be provided long-term protection by their incorporation into hydrophobic domains of soil organic matter.…”
Section: Carbohydratesmentioning
confidence: 98%
“…ER1 FA and ER3-NaOH HA were extracted from soil with sodium hydroxide (c (eq)"0.1 mol/L), ER2-2 HA was extracted with sodium pyrophosphate (c(eq)"0.1 mol/L). The samples from surface water HEN1 and HEN2 were preparated without separating a FA and HA fraction [6].…”
Section: Methodsmentioning
confidence: 99%
“…In J.B. Jahnel ( ) · F.H. Frimmel Engler-Bunte-Institut der Universita¨t Karlsruhe, Bereich Wasserchemie, D-76128 Karlsruhe, Germany aquatic HS up to 2% nitrogen have been determined usually [6]. The common method for nitrogen characterization studies is the classical acid hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Furthermore other organic molecules like amino acids, sugars and peptides can be incorporated leading to a broad range of different structural features. 42,43 Unfortunately, the very low concentration of those natural iron chelators in seawater makes the detection and characterization of them challenging. 44 Being aware of the importance of those natural macromolecules for marine microorganisms it is of large interest to nd synthetic compounds that are comparable to AHS, regarding their iron binding and transport properties in sea water, as well as their capability of providing bioavailable iron to algae.…”
mentioning
confidence: 99%